Transcranial magnetic stimulation to visual cortex induces suboptimal introspection. (August 2017) - Peters, Megan A.K.; Fesi, Jeremy; Amendi, Namema; Knotts, Jeffrey D.; Lau, Hakwan; Ro, Tony
Abstract: Blindsight patients with damage to the visual cortex can discriminate objects but report no conscious visual experience. This provides an intriguing opportunity to allow the study of subjective awareness in isolation from objective performance capacity. However, blindsight is rare, so one promising way to induce the effect in neurologically intact observers is to apply transcranial magnetic stimulation (TMS) to the visual cortex. Here, we used a recently-developed criterion-free method to conclusively rule out an important alternative interpretation of TMS-induced performance without awareness: that TMS-induced blindsight may be just due to conservative reporting biases for conscious perception. Critically, using this criterion-free paradigm we have previously shown that introspective judgments were optimal even under visual masking. However, here under TMS, observers were suboptimal, as if they were metacognitively blind to the visual disturbances caused by TMS. We argue that metacognitive judgments depend on observers' internal statistical models of their own perceptual systems, and introspective suboptimality arises when external perturbations abruptly make those models invalid – a phenomenon that may also be happening in actual blindsight.